Kejadian Stunting Balita ditinjau dari Aspek Kunjungan Posyandu dan Perilaku Pemberian ASI Eksklusif - Zuhrupal Hadi; Ahmad Zacky Anwary; Asrinawaty Asrinawaty (Jurnal Akademika Baiturrahim Jambi, 2022)
This research is an analytical survey with a Case Control approach with a ratio of 1: 2. The number of samples was 123 respondents with a quota sampling technique. The collection of data on the incidence of stunting in children under five was obtained from secondary data in Banjarmasin Kuin Raya Public Health Services, while data on maternal age, mother's education level, history of visits to posyandu and history of exclusive breastfeeding were obtained by interview method using a questionnaire. Data were analyzed using univariate and bivariate statistical Chi Square tests using a computer program with a 95% confidence level. Based on the results of research in Banjarmasin Kuin Raya Public Health Services working area, it was found that the history of visits of mothers who have children under five to posyandu was more that 46 (37.4%) were less active compared to 38 (30.9%) who were active and 39 (30.9%) who were inactive. (31.7%), while the history of breastfeeding was 77 (62.6%) non-exclusive breastfeeding more than exclusive breastfeeding as much as 46 (37.4%). Based on statistical tests, it was found that there was no significant relationship between history of visits to posyandu and history of exclusive breastfeeding with the incidence of stunting in children under five in Banjarmasin Kuin Raya Public Health Services working area